P631 Development and validation of a clinical scoring tool for predicting treatment outcomes with vedolizumab in patients with ulcerative colitis. (25th January 2019) - Dulai, P S; Singh, S; Vande Casteele, N; Meserve, J; Winters, A; Chablaney, S; Aniwan, S; Shashi, P; Kochhar, G; Weiss, A; Koliani-Pace, J L; Gao, Y; et al.
Abstract: Background: We created and validated a clinical decision support tool (CDST) for vedolizumab (VDZ) therapy in active ulcerative colitis (UC). Methods: To identify factors associated with corticosteroid-free remission (CSFREM; full Mayo score ≤2, no sub-score >1), logistic regression analyses were run on data from the GEMINI 1 VDZ trial for UC (derivation set; n = 620) and used to develop a CDST. Correlations between VDZ exposure, onset of action, and efficacy across predicted-probability groups were explored, and the CDST was externally validated in an observational cohort of VDZ-treated UC patients (validation set; n = 199). Results: Factors independently associated with CSFREM were absence of previous tumour necrosis factor antagonist exposure (+3 points), disease duration ≥2 years (+3 points), baseline endoscopic activity (moderate vs. severe) (+2 points), and baseline albumin concentration (+0.65 points per g/l). Patients were stratified into low (≤26 points), intermediate (>26 to ≤32 points), or high (>32 points) probability of response groups. The higher probability group more rapidly achieved symptom activity reductions and attained higher rates of CSFREM ( p < 0.001). In the validation set, a 26-point cut-off value showed high sensitivity (93%) for identifying non-responders. A statistically significant linear relationship was observed between VDZ exposure, probability groups, and efficacy in the derivation set ( p < 0.001). In the validation set, only the low–intermediate probability group benefited from VDZ interval shortening for lack of response ( p = 0.02). Conclusions: We developed and externally validated a CDST with good discriminative performance for predicting CSFREM with VDZ in UC patients. Pending further validation, this tool could be a helpful aid in identifying patients who would benefit from VDZ interval shortening due to insufficient response. (GEMINI 1: NCT00783718).